Implementasi Algoritma Apriori Terhadap Data Penjualan di Toko Roti Ganda Pematangsiantar - Tri Ayu Lestari; Ratih Ramadhanti; Agus Perdana Windarto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The tight market competition, especially for the sale of bread in Pematang Siantar City, makes all bakeries in that city have to maximize the quality of goods to increase sales and adjust consumer interest in the amount of goods produced. This research took place at the double bakery shop because this shop was the most popular. It aims to build a sales system by applying the apriopri algorithm data mining method in calculating sales data and turnover income from consumers through selecting the products that consumers are most interested in. Sources of data from this study were obtained through interviews and direct observation of consumers.